Optimization of Extraction Parameters for Phenolics and Flavonoids from Peony (Paeonia lactiflora) Flowers Using Ultrasound-Assisted Extraction - Jasmin, Faida; Handayani, Andi Ika Julianti; Akmal, Tubagus (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Peony (Paeonia lactiflora) flowers, celebrated for their aesthetic and bioactive attributes, possess potential as natural antioxidant sources owing to their elevated phenolic and flavonoid concentrations. This study employed ultrasound-assisted extraction (UAE) and response surface methodology (RSM) to optimize the extraction parameters for phenolic and flavonoid compounds. The Box-Behnken Design using method Ultrasoud Assisted Extraction determined the optimal extraction parameters of Paeonia lactiflora flowers to be 49% ethanol concentration, a liquid-to-solid ratio of 50 mL/g, and an extraction time of 22 minutes. The parameters yielded a total phenolic content (TPC) of 205.463 mg GAE/g DW and a total flavonoid content (TFC) of 95.465 mg QE/g DW. The results underscore the significance of the liquid-to-solid ratio as a critical factor in extraction efficiency, while ethanol concentration and extraction duration exhibited considerable interactive effects. The findings confirm the efficacy of UAE as a sustainable and efficient technique for extracting bioactive components from Paeonia lactiflora, indicating its potential use in pharmaceuticals and nutraceuticals. Future research should explore the antioxidant activity and IC50 values of these extracts for expanded therapeutic use.